Oleoylethanolamide Protects against Acute Ischemic Stroke by Promoting PPARα-Mediated Microglia/Macrophage M2 Polarization - Ying Li; Yanan Zhang; Qing Wang; Chuang Wu; Guicheng Du; Lichao Yang (MDPI AG, 2023)
Oleoylethanolamide (OEA) has been demonstrated to be a feasible protectant in ischemic stroke. However, the mechanism for OEA-afforded neuroprotection remains elusive. The present study aimed to investigate the neuroprotective effects of OEA on peroxisome proliferator-activated receptor α (PPARα)-mediated microglia M2 polarization after cerebral ischemia. Transient middle cerebral artery occlusion (tMCAO) was induced for 1 h in wild-type (WT) or PPARα-knock-out (KO) mice. Mouse small glioma cells (BV2) microglia and primary microglia cultures were used to evaluate the direct effect of OEA on microglia. A coculture system was used to further elucidate the effect of OEA on microglial polarization and ischemic neurons' fate. OEA promoted the microglia switch from an inflammatory M1 phenotype to the protective M2 phenotype and enhanced the binding of PPARα with the arginase1 (Arg1) and Ym1 promoter in WT mice but not in KO mice after MCAO. Notably, the increased M2 microglia caused by OEA treatment were strongly linked to neuron survival after ischemic stroke. In vitro studies confirmed that OEA shifted BV2 microglia from (lipopolysaccharide) LPS-induced M1-like to M2-like phenotype through PPARα. Additionally, the activation of PPARα in primary microglia by OEA led to an M2 protective phenotype that enhanced neuronal survival against oxygen-glucose deprivation (OGD) in the coculture systems. Our findings demonstrate the novel effects of OEA in enhancing microglia M2 polarization to protect neighboring neurons by activating the PPARα signal, which is a new mechanism of OEA against cerebral ischemic injury. Therefore, OEA might be a promising therapeutic drug for stroke and targeting PPARα-mediated M2 microglia may represent a new strategy to treat ischemic stroke.